Peran Konsumsi Air Minum Isi Ulang terhadap Pengurangan Sampah Plastik Sekali Pakai di Kabupaten Bone Bolango: Tinjauan Teoretis dan Empiris - Dudiyanto Pakaya; Mahludin S. Baruwadi; Hasim Hasim (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2025)
The increase in the consumption of bottled drinking water has become one of the main contributors to the generation of single-use plastic waste in various regions, including Bone Bolango Regency. This study aims to examine the role of refillable drinking water consumption in reducing household plastic waste and analyze it through the perspective of philosophy of science, including aspects of onology, epistemology, and axiology. The research uses a qualitative descriptive method with a literature review approach, empirical data analysis from government reports, and field observation. The results of the study show that the consumption of refillable drinking water contributes significantly to reducing the volume of plastic waste while increasing people's ecological awareness. From an ontological perspective, this phenomenon represents a change in consumption patterns that are more environmentally friendly. Epistemologically, the research confirms the importance of scientific knowledge in understanding the relationship between consumption behavior and ecological impacts. Meanwhile, from an axiological perspective, the research emphasizes the value of the benefits of science in shaping sustainable consumption behavior and encouraging the birth of more ethical and sustainability-oriented environmental policies. Thus, this study contributes to the development of plastic waste management strategies while strengthening the role of the community in realizing a healthier and more sustainable ecosystem.